Information system for web-based financial management in Kud Lubuk Karya: sistem informasi manajemen keuangan berbasis web pada kud lubuk karya - Ramba lovega, Desi chardyola Sari; Lesmana, Lido Sabda; Dwi Winarti; Purnomo, Wulan Andang; Tri Yuniko, Fauzi; Elinda Revita (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2024)
The financial management of a cooperative is the mobilization, organization and direction of human efforts to make effective use of materials and facilities to achieve a goal. In this savings and loan process, the funds in the Lubuk Karya Village Unit Cooperative (KUD) try professionally to manage finances with the aim of prospering the economic life of the group. Cooperative fund management must be carried out effectively and efficiently, this condition also needs to be managed by implementing modern management functions. The Lubuk Karya Village Unit Cooperative (KUD) is a financial management process such as money coming in and money going out that is often inaccurate. So that the process of accuracy of old data with new data often occurs inappropriately. This problem occurs because the data recording system is still manual and has not been integrated into the database system. The financial management system is a system that has been integrated with the database, which is expected to be able to manage the financial reports of members of the Lubuk Karya KUD in a transparent manner. So as to provide satisfaction for system users or cooperative members to get accurate information. Because the sources of financial funds that will be managed transparently are sourced from several types, namely from fertilizer factories, USP, Scales as well as the expenditure process for renting heavy equipment at the Lubuk Karya KUD.